Reading 360 Level 6 Book 7: Kim Ann and The Yellow Machine - Palmer, Candida (Ginn and Company Ltd, 1993)
This book is to be used to reinforce the vocabulary in enjoyable new contexts.
Keywords: Juvenile literature-Fiction